Antidiabetic activity of Berberis brandisiana is possibly mediated through modulation of insulin signaling pathway, inflammatory cytokines and adipocytokines in high fat diet and streptozotocin-administered rats - Mehdi, Shumaila; Mehmood, Malik Hassan; Ahmed, Mobeen Ghulam; Ashfaq, Usman Ali (Frontiers in Pharmacology, 2023)
Medicinal plants play a key role in protection of chronic non-communicable ailments like diabetes, hypertension and dyslipidemia. Berberis brandisiana Ahrendt (Berberiaceae) is traditionally used to treat diabetes, liver problems, wounds, arthritis, infections, swelling and tumors. It is also known to be enriched with multiple phytoconstituents including berbamine, berberine, quercetin, gallic acid,, caffeic acid , vanillic acid, benzoic acid, chlorogenic acid, syringic acid, p- coumaric acid, m-coumaric acid and ferulic acid. . The efficacy of Berberis brandisiana has not been established yet in diabetes. This study has been planned to assess the antidiabetic activity of Berberis brandisiana in high fat diet and streptozotocin (HFD/STZ)-induced - diabetes using animals. Administration of aqueous methanolic extract of Berberis brandisiana (AMEBB) and berbamine (Berb) for 8 weeks caused a dose dependent marked (p ˂ 0.01) rise in serum insulin and HDL levels with a significant decline (p ˂ 0.01) in glucose, triglycerides, HbA1c, cholesterol, LDL, LFTs and RFTs levels when compared with only HFD/STZ administered rats. AMEBB and Berb also modulated inflammatory biomarkers (TNFα, IL-6) and adipocytokines (leptin, adiponectin and chemerin). AMEBB and Berb treated rats showed a marked increase (p ˂ 0.001) in catalase levels (units/mg) in pancreas (42.4 ± 0.24, 47.4 ± 0.51) and superoxide dismutase levels (Units/mg) in pancreas (34.8 ± 1.46, 38.2 ± 0.58) respectively while a significant (p ˂ 0.01) decrease in serum melondialdehyde levels (nmol/g) in pancreas (7.34 ± 0.17, 6.22 ± 0.22) compared to the data of only HFD/STZ fed rats. Histopathological studies of pancreas, liver, kidney, heart and aorta revealed restoration of normal tissue architect in AMEBB and Berb treated rats. When mRNA expressions of candidate genes were assessed, AMEBB and Berb showed up regulation of IRS-1, SIRT-1, GLUT-4 and down regulation of ADAM17. These findings suggest that AMEBB and Berb possess antidiabetic activity, possibly due to its effect on oxidative stress, glucose metabolism, inflammatory biomarkers, and adipocytokines levels. Further upregulation of IRS-1, SIRT1, GLUT4 and downregulation of ADAM17, demonstrated its potential impact on glucose homeostasis, insulin resistance, and chronic inflammatory markers. Thus, this study provides support to the medicinal use of Berberis brandisiana in diabetes.